A bizarre new species of Triclistus Förster (Hymenoptera: Ichneumonidae; Metopiinae) from Amazonia - Sääksjärvi, Ilari Eerikki; Bordera, Santiago (Zootaxa, 2015)
A new bizarre new species of Metopiinae, Triclistus amazopeikkus sp. nov., is described and illustrated. The new species was collected from the lowland Peruvian Amazonia.